ORAL TRADITION AND DAILY READING: PILLARS FOR THE DEVELOPMENT OF CRITICAL THINKING IN SECONDARY SCHOOL STUDENTS - Ester Rondón Chinome; Johana Astrid Granados V. (LÍNEA IMAGINARIA, 2025)
This research analyzes oral tradition and daily reading as fundamental elements for the development of critical thinking among secondary school students in Colombia. Using a qualitative methodology based on documentary analysis, multiple academic sources were examined that demonstrate the relevance of these pedagogical practices in strengthening communicative and cognitive skills. The main objective was to determine how the integration of oral tradition and daily reading habits contribute to the development of critical thinking skills in students from sixth to ninth grade. The methodology used was based on the interpretive analysis of scientific documents, research articles, and empirical studies related to the topic, applying the constant comparison method for categorizing and analyzing information. The main findings reveal that oral tradition acts as a cultural preservation mechanism that stimulates critical reflection and argumentative dialogue, while daily reading strengthens the interpretive and analytical skills necessary for critical thinking. The research concludes that both practices, when systematically implemented in the context of basic secondary education, generate a significant impact on the development of critical and reflective citizens. These results are particularly relevant to the Colombian educational system, where strengthening critical thinking is a priority in the comprehensive education of students. The pedagogical implications suggest the need to integrate teaching strategies that combine traditional oral tradition with systematic reading practices to optimize students' cognitive and communicative development.